Blast injuries to the lung: epidemiology and management - Mackenzie, Iain M. J. (The Royal Society, 2011)
Lung injury is frequently a component of the polytrauma sustained by military personnel surviving blast on the battlefield. This article describes a case series of the military casualties admitted to University Hospital Birmingham's critical care services (role 4 facility), during the period 1 July 2008 to 15 January 2010. Of the 135 casualties admitted, 107 (79.2%) were injured by explosive devices. Plain chest films taken soon after arrival in the role 4 facility were reviewed in 96 of the 107 patients. In 55 (57.3%) films a tracheal tube was present. One or more radiological abnormalities was present in 66 (68.75%) of the films. Five patients met the consensus criteria for the definition of adult respiratory distress syndrome (ARDS). The majority of casualties with blast-related lung injury were successfully managed with conventional ventilatory support employing a lung protective strategy; only a small minority received non-conventional support at any time in the form of high-frequency oscillatory ventilation. Of those casualties who survived to be received by the role 4 facility, none subsequently died as a consequence of lung injury.